Community Therapist Response to Technology-Assisted Training in Exposure Therapy for Childhood Anxiety Disorders. Issue 3 (May 2022) - Whiteside, Stephen P. H.; Biggs, Bridget K.; Dammann, Julie E.; Tiede, Michael S.; Hofschulte, Deanna R.; Brennan, Elle
Despite the efficacy of exposure for childhood anxiety disorders (CADs), dissemination has been unsuccessful. The current study examined community-therapist response to a brief (90-minutes) training in technology-assisted exposure therapy for CADs. The results indicated that therapists found the training in the therapy approach and technology acceptable, despite endorsing mainly non-exposure-based practice prior to the training. Training also increased positive beliefs about exposure, t (23) = 4.32, p  < .000, that persisted 6 months later, t (23) = 4.56, p  < .000. In addition, the number of therapists reporting an intention to implement exposure increased substantially from baseline (41.7%) to post-training (83.3%), with many therapists (70.8%) reporting use of exposure within the 6 months following training. However, automatically recorded data indicated little use of the technology. Results suggest that a dissemination message focusing on exposure is acceptable and has the potential to increase the use of this central treatment component.